Gen Z Consumer Trends: Understanding The Next Wave Of Buying Behavior - Sjahruddin, Herman; Adif, Riandy Mardhika (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This article offers a comprehensive exploration of Generation Z consumer trends within the context of PT. Murza Utama. The study investigates the relationships between Brand Preference (BP), Brand Innovation (BI), Business Ethics (BE), and Buying Decision (BD). The direct test results indicate that while the impact of Brand Preference on Business Ethics and Buying Decision may not be statistically significant, Brand Innovation significantly influences Business Ethics and Buying Decision. The indirect test results suggest a nuanced relationship between Brand Preference and Buying Decision, mediated by Business Ethics. The findings underscore the importance of integrating both innovation and ethical practices in shaping consumer behavior. Businesses, including PT. Murza Utama, are advised to adopt strategies that embrace innovation while maintaining a strong ethical foundation to effectively engage Generation Z consumers.